2006
DOI: 10.1007/s10750-005-1371-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Subtidal Macrobenthic Distribution in Relation to Abiotic Conditions in the Lima Estuary, NW of Portugal

Abstract: During the summer of 2002, sampling was carried out in the Lima estuary in order to compare the pattern of the macrobenthic community's distribution in relation to physical and chemical variables. A total of 54 macrobenthic taxa were identified. Abundance, biomass and specific diversity varied among the twenty stations. Abundance ranged from 212 to 9856 ind./m 2 , with an average of 1581 ind./m 2 . Abra alba presented the highest density corresponding to 39.1% of the total specimens gathered, followed by Hedis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 29 publications
3
52
0
2
Order By: Relevance
“…In the present study, differences in temperature and salinity (Sousa et al 2006). The comparison of subtidal sediment characteristics determined in the present study with those reported by Alves (1996) and Sousa (2003) indicates that no significant changes occurred in recent years, and the sediments were predominantly sands.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…In the present study, differences in temperature and salinity (Sousa et al 2006). The comparison of subtidal sediment characteristics determined in the present study with those reported by Alves (1996) and Sousa (2003) indicates that no significant changes occurred in recent years, and the sediments were predominantly sands.…”
Section: Discussionmentioning
confidence: 53%
“…Abundances recorded in subtidal stations, with more pronounced changes in salinity between low and high tide, were lower than in intertidal sites. As well, 2004 and 2005 subtidal abundances were inferior to those found in 2002 when salinity values were considerably lower (Sousa et al 2006).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations